2008
DOI: 10.1021/ol800259s
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (±)-Mersicarpine

Abstract: The first total synthesis of the indole alkaloid mersicarpine is reported. Key steps include a beta-dicarbonyl radical cyclization, as well as an oxidation of the benzopyrrole moiety to establish the masked 1,2-dicarbonyl functionality. An X-ray crystal structure and discussion of the 1H NMR behavior of the natural product are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 12 publications
(13 reference statements)
6
87
0
Order By: Relevance
“…These conditions simultaneously deprotected the amino group, so the Boc unit had to be reinstalled. Compound 179 , thus obtained, had already been converted into (±)‐mersicarpine 180 by Kerr and coworkers in three steps, so the sequence in Scheme represents a formal synthesis of this unusual Kopsia alkaloid …”
Section: Applications To Synthesismentioning
confidence: 89%
See 1 more Smart Citation
“…These conditions simultaneously deprotected the amino group, so the Boc unit had to be reinstalled. Compound 179 , thus obtained, had already been converted into (±)‐mersicarpine 180 by Kerr and coworkers in three steps, so the sequence in Scheme represents a formal synthesis of this unusual Kopsia alkaloid …”
Section: Applications To Synthesismentioning
confidence: 89%
“…Compound 179, thus obtained, had already been converted into (AE)-mersicarpine 180 by Kerr and coworkers in three steps,s ot he sequence in Scheme 19 represents af ormal synthesis of this unusual Kopsia alkaloid. [54] Scheme 18. An alliance with the alkylative Birch reduction.…”
Section: Reactions Involving Crossover To the Cationic Manifoldmentioning
confidence: 99%
“…Later, Kerr et al . developed an intramolecular version of this reaction ( A to B , Figure ), which was applied to the total syntheses of mersicarpine and alsmaphorazine D . In an attempt to assemble welwitindolinone, the Rawal group observed that manganese(III)‐mediated oxidative cyclization between indole part and a tethered β‐ketoester unit occurred either at the indole C4‐position ( C to D ) or at the indole C2‐position ( C to E ) depending on the substituents at the indole C2‐position .…”
Section: Figurementioning
confidence: 99%
“…This intriguing molecule has attracted much attention, and four total syntheses, including ours, have been reported to date. [2][3][4][5] Chart 1 depicts our synthesis of mersicarpine (1). First, the quaternary carbon was constructed according to d'Angelo's procedure.…”
Section: Synthesis Of Mersicarpinementioning
confidence: 99%